Pentingnya Pendidikan Vokasi dalam Mengembangkan Ilmu Bisnis Maritim di Indonesia - Muhammad Zaki Raihansyah; Rangga Vania Abqari; Moh. Hisyam Alwafy; Mohammad Bachrul Syafa'at; Denny Oktavina Radianto (Pusat Riset dan Inovasi Nasional, 2024)
Vocational education in maritime business science is not only an obligation, but also an important foundation in preparing quality human resources capable of facing the complexity and dynamics that are developing rapidly in the maritime industry in Indonesia. This article is committed to diving deeply into the urgency and relevance of vocational education in building competencies that suit the needs of the maritime business sector, carefully analyzing the challenges that are obstacles, and offering solid solutions and recommendations to improve the quality of vocational education in order to answer the industry's call with effective. In order to holistically understand Indonesia's maritime potential, which includes all aspects such as sea transportation, export-import, fisheries sector, and marine tourism, this article highlights the important role of vocational education in forming a competitive workforce on the globalization stage. While the opportunities are wide open, this article also highlights a number of challenges that lie ahead, including limited educational infrastructure, the irrelevance of the curriculum to industry needs, and the lack of technology integration in the learning process. By formulating strategic steps, this article hopes to formulate a strong solution, ensure that maritime business vocational education becomes more adaptive and responsive to industry dynamics, and ensure that Indonesia continues to move forward on the global competition map